Strategies to provide care to Non-COVID Patients in the COVID Era: An Experience from a Tertiary Care Institute in Northern India - Kishore, Surekha; Mohanty, Aroop; Hada, Vivek; Kumar, Subodh; Rath, Rama Shankar (Indian Journal of Community Health, 2021)
With the COVID-19 pandemic the health system is facing dual burden of cases, one being the COVID-19 or Severe Acute Respiratory Illness (SARI) cases and the second being the other Non-COVID cases. The Non-COVID cases due to the burden of the SARI cases became almost neglected by the Health System increasing the sufferings of the Non-COVID cases. In the current COVID times All India Institute of Medical Sciences, Gorakhpur continued to provide the health care to the Non-COVID cases. The current manuscript provides the detailed strategy and results of the various strategies used to provide care to such Non-COVID patients with minimum risk to the healthcare staff.